Control Strategy of True Time Delay Lines - Rabal, Heinrich Sebastian (2017)
This article presents the control of adjustable true time delays applied to an optical beamforming system. First is introduced the response of ring resonators of two and four ports and the cascade and lattice structures. The coupling factor and the phase modulation are employed as the control parameters for the adjustable group delay. The strategy of control is proposed and applied to a cascade of five ring resonators for producing wideband true time delays in the picosecond–nanosecond range with 2-GHz bandwidth and extremely low ripple. Ripples lower than 0.1% were obtained for the adjusted group delays. The proposed strategy can be simply extended if more resonators are added to increase the bandwidth of the system.